Markers of systemic inflammatory response, oxidative stress, and endothelial dysfunction in patients with arterial hypertension combined with rheumatoid arthritis with diastolic dysfunction - Ryndina, Nataliya (ScienceRise: Medical Science, 2019)
Introduction. In patients with rheumatoid arthritis (RA) in combination with arterial hypertension (AH) the early development of cardiovascular complications is caused by chronic systemic inflammation, a high level of pro-inflammatory cytokines and lipid peroxidation products (LPO). Aim of the research. For the purpose of early diagnosis of complications, study of the diastolic function of the left ventricle (LV) in patients with AH in combination with RA and determine the predictor value of LPO, endothelial function (EF), markers of a systemic inflammatory response regarding impaired LV diastolic function, and detection of exudate in the pericardial cavity. Materials and methods. We examined 96 patients with stage II of AH in combination with RA, 45 patients with stage II arterial hypertension and 31 healthy subjects. Patients underwent echocardioscopy and we determined the levels of isolated double bonds, Schiff’s bases, diene conjugates, diene ketones, malonic aldehyde, vitamins A, E, catalase, asymmetric dimethylargenini (ADMA), interleukin-1 beta (IL 1-B), interleukin-10 ( IL 10), a highly sensitive C-reactive protein (hs-CRP) and the level of final serum nitric oxide metabolites. Conclusins. The highest predictor value with respect to impaired LV diastolic function in AH patients in combination with RA was found in the indicator IL 1-B, AUC 0.882, sensitivity 72.15%, specificity 100% with an optimal distribution point >9.67 pg / ml, and relatively for detecting fluid in the pericardial cavity at an ADMA AUC of 0.913 with an optimal distribution point >0.841 μmol / L, sensitivity 94.12%, specificity 85.53%